2012
DOI: 10.5665/sleep.1634
|View full text |Cite
|
Sign up to set email alerts
|

Daily Sleep and Fatigue Characteristics in Nulliparous Women during the Third Trimester of Pregnancy

Abstract: Results suggest that interventions designed to increase sleep duration and decrease depressive symptoms have the potential to prevent, ameliorate, or reduce fatigue in pregnant women. Depressive symptoms during pregnancy likely share some psychological and behavioral tendencies with fatigue and/or sleep disturbance which may complicate the evaluation of intervention effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 38 publications
3
30
1
4
Order By: Relevance
“…Facco et al in Chicago analysed self-administered questionnaires from women in early pregnancy and again in the third trimester and showed that mean sleep duration dropped from 7.4 hours early in pregnancy to 7 hours in late pregnancy [9]. In a small Taiwanese study using actigraphy to measure sleep duration in nulliparous women the mean duration of total night time sleep in the third trimester was 6.4 (± 1.0) hours [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Facco et al in Chicago analysed self-administered questionnaires from women in early pregnancy and again in the third trimester and showed that mean sleep duration dropped from 7.4 hours early in pregnancy to 7 hours in late pregnancy [9]. In a small Taiwanese study using actigraphy to measure sleep duration in nulliparous women the mean duration of total night time sleep in the third trimester was 6.4 (± 1.0) hours [16]. …”
Section: Discussionmentioning
confidence: 99%
“…During the second trimester, daytime sleepiness improves. During the third trimester there is an increase in sleep disruptions with typically 3–5 awakenings per night, more daily naps 49 , diminished daytime alertness, more disturbed dreams 50 , and approximately 21% report disturbed sleep at levels consistent with a diagnosis of insomnia disorder 47,51 . Decreased sleep efficiency, increased wake after sleep onset, increased total sleep time (decreased by third trimester), increased stage 1 and 2 sleep, and decreased REM sleep (during late pregnancy) have been noted by PSG recordings 5255 .…”
Section: Pregnancymentioning
confidence: 99%
“…Pregnancy is characterized by substantial changes in sleep patterns, such as increased frequency of insomnia symptoms, including night-wakings, daytime fatigue, and in some cases, also difficulties falling asleep and waking up too early in the morning (Manber et al 2013;Mindell and Jacobson 2000;Skouteris et al 2009a;Tsai et al 2012). Although most of the studies in this field are based on self-reported measures of sleep, studies that used objective sleep measures, such as actigraphy and polysomnography (PSG), support these findings and suggest that in comparison to nonpregnant women, pregnant women have lower sleep efficiency, more frequent night-wakings and longer night-wakings and spend more time in light sleep and less time in deep sleep and REM sleep (Hertz et al 1992;Wilson et al 2011).…”
Section: Introductionmentioning
confidence: 99%